2012
DOI: 10.1097/mph.0b013e3182422844
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Cell Disease Subphenotypes in Patients From Southwestern Province of Saudi Arabia

Abstract: Sickle cell disease (SCD) is common in the Eastern and Southwestern (SW) Provinces of Saudi Arabia. We studied 159 patients with SCD to better characterize its phenotype in the SW Province, where patients usually have a HBB haplotype of African origin. All cases had history and examination, chart review, and laboratory testing. Blood tests were obtained during steady state and included: complete blood count, reticulocytes, hemoglobin electrophoresis, lactate dehydrogenase, and G6PD level. HBB haplotype and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…However, some HbF remains to be heterogeneously transcribed with variable expression levels across HbF red blood cells (F cells) [32]. Initial observations suggested that HBB haplotypes also have an effect on the severity of SCD [8,9]. The Bantu haplotype being the less favourable and the Indian-Arab haplotype associated to the least severity; as the latter is associated with higher HbF levels [33], due to a single nucleotide polymorphism (SNP) upstream of the β-globin gene (rs7482144 or Xmn- G γ), characteristically present in Indian Arab and Senegal haplotypes [34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some HbF remains to be heterogeneously transcribed with variable expression levels across HbF red blood cells (F cells) [32]. Initial observations suggested that HBB haplotypes also have an effect on the severity of SCD [8,9]. The Bantu haplotype being the less favourable and the Indian-Arab haplotype associated to the least severity; as the latter is associated with higher HbF levels [33], due to a single nucleotide polymorphism (SNP) upstream of the β-globin gene (rs7482144 or Xmn- G γ), characteristically present in Indian Arab and Senegal haplotypes [34].…”
Section: Resultsmentioning
confidence: 99%
“…Four haplotypes are associated with HbS in Africa (Benin, Bantu/Central African Republic (CAR), Senegal and Cameroon) and the fifth is thought to have arisen in India and/or the Arabian Peninsula (Arab/Hindu) [6,7]. It has been suggested that these haplotypes also have an effect on the severity of the disease through their genetically-determined effect on HbF level [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…High rates of α-thalassemia are also observed in the Middle East with estimates of up to 50% of the population carrying deletional (−α 3.7 and −α 4.2 ) or nondeletional (α Constant Spring and α TSaudi ) forms of α-thalassemia (36). In cohorts of Hb SS populations from the Middle East, frequencies of the (−α) chromosome are 0.39 – 0.48 (37, 38). Migration patterns have led to the distribution of α-thalassemia deletion and non-deletion mutations in non-malaria endemic regions.…”
Section: Geographic Variability Of α-Thalassemia In Sickle Cell Diseasementioning
confidence: 99%
“…ickle cell disease (SCD) is a monogenic, inherited anemia with variable clinical manifestations and associated variable disease severity (1), since some patients present with severe complications, while others do not present with any SCD complications (2). Besides vasoocclusive crisis (VOC), osteomyelitis is a common complication of SCD and is a major cause for hospitalization of SCD patients (3).…”
mentioning
confidence: 99%